1954
DOI: 10.1111/j.2042-7158.1954.tb10983.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Toxicity of Bread Additives to Rats

Abstract: Summary Bread containing 50 times the normal concentration of chlorine dioxide, propyl gallate and butylated hydroxyanisole, polyoxyethylene (8) monostearate, or sodium propionate as 75 per cent, of the diet for 1 year did not harmfully affect growth or mortality of rats. The high concentrations of polyoxyethylene (8) monostearate, sodium propionate, antioxidants and chlorine dioxide had no detectable effect on organ weights or on histopathology of the tissues. No evidence was obtained that the simultaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1956
1956
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…No diarrhea was observed in these animals nor was there any indication of hematuria. Absence of pathology after feeding Myrj 45 at abnormally high levels for prolonged periods of time confirmed studies by others with rats, cats, and humans (1,2,3,7,8,12,13,14,20). Eagle and Poling ( 4 ) present their pathological findings in terms of per cent, a procedure'that can be somewhat misleading when groups are as small (7 to 10) as those examined.…”
Section: Discussionsupporting
confidence: 84%
“…No diarrhea was observed in these animals nor was there any indication of hematuria. Absence of pathology after feeding Myrj 45 at abnormally high levels for prolonged periods of time confirmed studies by others with rats, cats, and humans (1,2,3,7,8,12,13,14,20). Eagle and Poling ( 4 ) present their pathological findings in terms of per cent, a procedure'that can be somewhat misleading when groups are as small (7 to 10) as those examined.…”
Section: Discussionsupporting
confidence: 84%
“…In treated females, a low incidence of renal tubular degeneration and glomerulonephritis was observed (Graham et al, 1954as reported in CIR, 1974. Some animals were necropsied at weeks 13 and 26 and at study termination.…”
Section: The Ntp Concluded: "Under the Conditions Of This Bioassay Pmentioning
confidence: 62%
“…Propionic acid and its calcium, potassium and sodium salts are authorised as food additives in the EU in accordance with Annex II to Regulation ( normal constituent of foods, and despite only one chronic toxicity study (1-year) being available (Graham et al, 1954), allocated an acceptable daily intake (ADI) for man "not limited"…”
Section: Information On Existing Authorisations and Evaluationsmentioning
confidence: 99%